EFEKTIFITAS PENGGUNAAN APLIKASI ASAP DIGITAL DALAM MENCEGAH KEBAKARAN HUTAN DAN LAHAN PROVINSI JAMBI - Riko Alpauzi Roni; Makmun Wahid; Citra Darminto (Universitas Riau Kepulauan, 2023)
ABSTRACTAsap Digital is a monitoring tool for early detection of forest and land fires. This tool has a number of features ranging from monitoring hot spots, CCTV, and personnel. The existence of this tool is based on the problem of forest and land fires which occur almost every year with a variety of the number of incidents and the area of land burned. This research aims to find out how effective the use of Asap Digital is in preventing forest and land fires in Jambi Province. in this context there are several outlines such as the effectiveness of Asap Digital, and the factors that most influence the success of Asap Digital. There are 5 dimensions offered by Richard M. Steers as a basis for analysis starting from adaptation, productivity, job satisfaction, profit ability, and resource search. Collecting data through qualitative descriptive research methods namely interviews, observation, and documentation. So that the data obtained is accurate and credible, the purposive sampling model is a way to determine informants with consideration of authority and understanding of Asap Digital. After the data is obtained, data analysis starting from collection, reduction, presentation, and drawing conclusions becomes the method of analysis in this study. The results of this study indicate that the use of Asap Digital has been quite effective through Hot Spot monitoring. However, this is inseparable from the constraints on productivity indicators that are less than optimal due to the high cost of CCTV services so that several CCTV points were found that were dead due to default. this will have an impact on the benefits aspect of the Asap Digital itself. ABSTRAKAsap Digital merupakan alat pemantau deteksi dini kebakaran hutan dan lahan. alat ini terdapat sejumlah fitur mulai dari pantauan titik panas, CCTV, dan personel. Kehadiran alat tersebut didasari oleh persoalan kebakaran hutan dan lahan yang hampir setiap tahun terjadi dengan ragam jumlah kejadian dan luas lahan terbakar. Penelitian ini hadir dengan tujuan mengetahui sejauh mana efektivitas penggunaan Asap Digital ini berjalan demi mencegah kebakaran hutan dan lahan Provinsi Jambi. dalam konteks ini terdapat beberapa garis besar seperti efektifitas Asap Digital, dan faktor yang paling mempengaruhi keberhasilan Asap Digital. Ada 5 dimensi yang ditawarkan oleh Richard M. Steers sebagai dasar analisa mulai dari adaptasi, produktivitas, kepuasan kerja, kemampuan berlaba, dan pencarian sumber daya. Pengumpulan data melalui metode penelitian deskriptif kualitatif yakni wawancara, obsevasi, dan dokumentasi. Agar data yang diperoleh tepat dan kredibel, model purposive sampling menjadi cara untuk menentukan informan dengan pertimbangan kewenangan dan kepahaman terhadap Asap Digital. Setelah data yang diperoleh, analisa data mulai dari pengumpulan, reduksi, penyajian, dan penarikan kesimpulan menjadi metode analisis dalam penelitian ini. Hasil penelitian ini menunjukkan bahwa penggunaan Asap Digital telah cukup efektif melalui pantauan Hot Spot. Namun tidak terlepas dari kendala indikator produktivitas yang kurang maksimal disebabkan mahalnya biaya layanan CCTV sehingga ditemukan beberapa titik CCTV yang mati akibat gagal bayar. hal ini akan berdampak pada aspek manfaat dari Asap Digital itu sendiri.